2020
DOI: 10.1093/glycob/cwaa052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 22 N-glycosites on spike glycoprotein of SARS-CoV-2 and accessible surface glycopeptide motifs: Implications for vaccination and antibody therapeutics

Abstract: Coronaviruses hijack human enzymes to assemble the sugar coat on their spike glycoproteins. The mechanisms by which human antibodies may recognize the antigenic viral peptide epitopes hidden by the sugar coat are unknown. Glycosylation by insect cells differs from the native form produced in human cells, but insect cell-derived influenza vaccines have been approved by the US Food and Drug Administration. In this study, we analyzed recombinant severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 41 publications
6
83
0
Order By: Relevance
“…As the S glycoprotein of SARS-CoV-2 is having 22 N-linked glycosylation sites occupied with complex and oligomannose type of glycans (Watanabe et al, 2020;Zhou et al, 2020), these glycans pose as interesting targets for targeted and novel antiviral development. However, understanding this glycan language is lagging behind the proteins due to its complex nature and existence of various conformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the S glycoprotein of SARS-CoV-2 is having 22 N-linked glycosylation sites occupied with complex and oligomannose type of glycans (Watanabe et al, 2020;Zhou et al, 2020), these glycans pose as interesting targets for targeted and novel antiviral development. However, understanding this glycan language is lagging behind the proteins due to its complex nature and existence of various conformations.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D structure of SARS-CoV-2 (PDB ID: 6WPS) deposited in Protein Data Bank (PDB) also reported having GlcNAc, a-D-Man, b-D-Man and a-L-Fucose and fucosylated Man 3 GlcNAc 2 at site N343 (Pinto et al, Preprint). In another study, (Zhou et al, 2020) analyzed the S glycoprotein secreted from the BTI-Tn-5B1-4 insect cells. Upon chymotrypsin and trypsin digestion and mass analysis, they revealed that all predicted 22 N-linked SARS-CoV-2 glycosylated sites are changed by high mannose N-glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, glycosylation of SARS-CoV-2 S vaccine candidates should be considered: DNA/RNA vaccines are produced in situ inside the patient and thus would carry native glycosylation; for recombinant subunit vaccines glycoengineering protocols may be applied. The hotspot of SARS-CoV-2, however, which is critical in binding to the ACE2 receptor, appears to be free from glycosylation 32 ; therefore, it may not be required to glycosylate corresponding peptide epitopes.…”
Section: Focus | Review Articlementioning
confidence: 99%
“…The SARS-CoV-2 spike is a type 1 fusion machine, responsible for virus-cell entry via ACE2 receptor interactions and TMPRSS2 protease activation in the endosome 8 . It is substantially glycosylated 9,10 . It is also divergent from other beta-coronavirus pathogens known to have infected humans 2 , and it continues to diversify 7 .…”
mentioning
confidence: 99%